Dynamic of recovery growth of intercropped soybean after maize harvest in maize–soybean relay strip intercropping system. (23rd November 2021) - Wu, Yushan; Gong, Wanzhuo; Yang, Feng; Wang, Xiaochun; Yong, Taiwen; Liu, Jiang; Pu, Tian; Yan, Yanhong; Yang, Wenyu
Abstract: Recovery growth is common in relay intercropping systems and is a useful practice to increase total productivity of these systems. A field experiment was conducted during 2014–2016 to investigate the phenotypic and physiological traits related to light interception and utilization changes and cultivars difference of soybean during the recovery growth period. Two cropping patterns (maize–soybean relay strip intercropping (RSI), analogous soybean monoculture (CK)) and two soybean cultivars (shade‐tolerant Nandou12 and shade non‐tolerant Jiuyuehuang ) were evaluated. During the co‐growth period, the growth of both two soybean cultivars was suppressed and showed a series of shade avoidance traits. After maize harvest, the LAI and leaflet number of intercropped soybean exhibited rapid growth, the LAI of Nandou12 (3.09) and Jiuyuehuang (1.32) recovered to 79% and 43% of corresponding CK level, respectively. Subsequently, final biomass of Nandou12 (3972.7 kg ha −1 ) and Jiuyuehuang (2263.3 kg ha −1 ) recovered 85.7% and 52% of corresponding CK level, respectively. Leaf blade thickness of Nandou12 recovered to the corresponding CK level, while Jiuyuehuang was not. Pn recovered to 84.5% and 82.8% of sole Pn at 80 days after soybean sowing in 2015 and to 72% and 91.2% at 66 days after soybean sowing in 2016 for Nandou12 and Jiuyuehuang, respectively. The above recovery process promoted the recovery of pod formation and grain yield. The yield of Nandou12 (1159.5 kg ha −1 ) has no significant difference between the CK level (1325.5 kg ha −1 ) but significantly higher than that of Jiuyuehuang (566.8 kg ha −1 ). Taken together, some recovery growth did occur in Jiuyuehuang, but it did not completely compensate for the growth reduction that occurred during the co‐growth period. Shade‐tolerant soybean cultivar has more stronger recovery growth ability in LAI, leaflet number, leaf thickness, and photosynthesis after maize harvest, which promoted the recovery growth of aboveground biomass and grain yield. Abstract : BLURB FOR ETOCRecovery growth is a useful practice to increase total productivity of relay intercropping systems. Understanding phenotypic and physiological traits related to light interception and utilization changes and cultivars difference of soybean during the recovery growth period is important for further breeding and screening cultivars of soybean to improve the light interception and utilization in intercropping systems.